Backscattering measurement of He 6 on Bi 209: critical interaction distance - Guimarães, V.; Kolata, J. J.; Aguilera, E. F.; Howard, A.; Roberts, A.; Becchetti, F. D.; Torres Isea, R. O.; Riggins, A.; Febrarro, M.; Scarduelli, V.; De Faria, P. N.; Monteiro, D. S.; et al. (American Physical Society, 2016)
Fil: Guimarães, V.. Universidade de Sao Paulo; Brasil. Institute de Physique Nucleaire d’Orsay; Francia